Statistical processing of transient parameters in biorhythms of cortex - Кузовик, Вячеслав Данилович; Гордєєв, Артем Дмитрович (Technology audit and production reserves, 2016)
Modern medicine is focused on the implementation of non-invasive diagnostic tools and forecasting body dysfunctions of operators in extreme activities. To evaluate psychophysical condition of operators, special software and expert systems are developed, but they have several disadvantages, the main of which are: the complexity of electroencephalographic data interpretation; imperfection of integral evaluation parameters of psychology health conditions of operators in extreme activities; usually no graphical interface designed for physician specialist. This paper presents a statistical approach to evaluating options of information and energy fields in cortex based on processing biopotentials of the cortex with accounting the psychological subgroups of operators. The present approach is a computerized expert system that provides medical-specialist to analyze quantitative parameters of stationary record signal and electroencephalogram transient, which in turn allows assessing and predicting psychophysiological cortex state of the operator. Algorithms of presented approach are based on the use of robust methods of data analysis and iterative simulation using Monte Carlo method. As a result of research it was obtained normalized values of cephalography, electroencephalography, blood tests for operators in extreme activity of a psychological subgroup, and graphical and analytical statistical regression model of tolerance, which is based on parameters of cephalography, electroencephalography and time. Due to the obtained results can not only assess the current psychophysiological state of the organism for operators in extreme activities, but also to predict its changes. The results of research can be used in the medical field of transplantology for donor selection or monitoring of the rehabilitation process after transplanting internal organs.